Strategi Pengawasan Pimpinan Dalam Meningkatkan Kinerja Pegawai Di Kantor Pangulu Nagori Siantar Estate Kabupaten Simalungun - Ismi Nurhasani (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
The purpose of this study was to determine the strategies used by leader in improving employee performance at the Pangulu Nagori Siantar Estate office Simalungun Regency. This study uses a qualitative descriptive approach that provides a clear and systematic description of the object under study in order to provide valid information and data related to existing facts and phenomena and is based on the intention to describe descriptively the supervisory strategy in improving employee performance in the Pangulu office. Based on the results of the study, it shows that Pangulu Nagori Siantar Estate implements a supervisory strategy in the office, namely Direct Control and Indirect Control, planning for results-oriented supervision strategies to be achieved within a period of one to five years by taking into account the potential, opportunities and constraints, there is no applicable punishment for employees who make mistakes and differences in employee character the leadership also evaluates to review employee performance and can prevent errors and deviations in employee performance in carrying out their work.